2021
DOI: 10.1080/23812346.2021.1940690
|View full text |Cite
|
Sign up to set email alerts
|

What does sustainability demand? An institutionalist analysis with applications to China

Abstract: In this paper we discuss if existing political and economic institutions can ensure sustainable futures. We do so by combining a global outlook with more specifically examining the situation in China. Present institutions foster growth, they are however weak at motivating actions that keep economies within an environmentally safe and socially just space. We especially note the challenges that strong focus on growth combined with ex post environmental regulations create for natural systems with tippingpoints. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…According to the negative effects of small-scale farmers in financial capital, it is necessary to increase farmers' income and consequently alleviate poverty to improve food security. 59 Therefore, it is recommended to cultivate higher-value products. 60 Moreover, it is suggested that those small-scale farmers participate in a variety of income-generating activities.…”
Section: Discussionmentioning
confidence: 99%
“…According to the negative effects of small-scale farmers in financial capital, it is necessary to increase farmers' income and consequently alleviate poverty to improve food security. 59 Therefore, it is recommended to cultivate higher-value products. 60 Moreover, it is suggested that those small-scale farmers participate in a variety of income-generating activities.…”
Section: Discussionmentioning
confidence: 99%
“…Governance is the mechanism by which power and transparency are established and practiced over time, and it is also about making decisions and maintaining the conditions for their successful execution [148]. It concerns who makes choices and how, particularly in regard to educational practices and evolving social structures; it also concerns who occupies positions of authority and responsibility and who should be held accountable [149,150].…”
Section: Key Barriers To the Successful Global Governance Of The Envi...mentioning
confidence: 99%
“…Fiscal capacity refers to local governments’ spendable finance in pursuing land development (He and Wu, 2005). Distrustful of private enterprise, local governments with strong fiscal capacity often select state agents instead of market agents for land development (Li and Chiu, 2020; Tan et al, 2021). In contrast, public–private partnerships appeal to local governments with weak fiscal capacity for land development (Cheng et al, 2018).…”
Section: Land Regime Rescaling Under China’s City-regionalism: a Conc...mentioning
confidence: 99%